DAMPAK METAVERSE TERHADAP PENDIDIKAN AGAMA KRISTEN - Esti Regina Boiliu (Sekolah Tinggi Teologia Wesley Methodist Indonesia, 2022)
In 1992, Metaverse was initially introduced. Although many people think of Metaverse as a new phrase, the concept is not. The Metaverse, on the other hand, was the focus of Zuckerberg's news release. Given that the metaverse will most likely pervade many aspects of human life in the next 15-20 years, influencing human life through leveraging technological advancements. This is why I wrote this article, which examines how the metaverse affects Christian Religious Education. The author employs a qualitative approach in writing this essay, relying on secondary data from a literature review study that, of course, includes a look at the metaverse and Christian Religious Education. According to the findings of this study, the metaverse has a significant impact on all aspects of human existence, including education. Christian Religious Education is the goal of education in this environment. As a result, Christian Religious Education has a critical role to play in preparing students for the metaverse, which is currently popular and will almost surely occur in real life in the future.